A new mouse model of Ehlers-Danlos syndrome generated using CRISPR/Cas9-mediated genomic editing - Yuko Nitahara-Kasahara; Shuji Mizumoto; Yukiko U. Inoue; Shota Saka; Guillermo Posadas-Herrera; Aki Nakamura-Takahashi; Yuki Takahashi; Ayana Hashimoto; Kohei Konishi; Shinji Miyata; Chiaki Masuda; Emi Matsumoto; et al. (The Company of Biologists, 2021)
Musculocontractural Ehlers-Danlos syndrome (mcEDS) is caused by generalized depletion of dermatan sulfate (DS) due to biallelic pathogenic variants in CHST14 encoding dermatan 4-O-sulfotransferase 1 (D4ST1) (mcEDS-CHST14). Here, we generated mouse models for mcEDS-CHST14 carrying homozygous mutations (1 bp deletion or 6 bp insertion/10 bp deletion) in Chst14 through CRISPR/Cas9 genome engineering to overcome perinatal lethality in conventional Chst14-deleted knockout mice. DS depletion was detected in the skeletal muscle of these genome-edited mutant mice, consistent with loss of D4ST1 activity. The mutant mice showed common pathophysiological features, regardless of the variant, including growth impairment and skin fragility. Notably, we identified myopathy-related phenotypes. Muscle histopathology showed variation in fiber size and spread of the muscle interstitium. Decorin localized diffusely in the spread endomysium and perimysium of skeletal muscle, unlike in wild-type mice. The mutant mice showed lower grip strength and decreased exercise capacity compared to wild type, and morphometric evaluation demonstrated thoracic kyphosis in mutant mice. The established CRISPR/Cas9-engineered Chst14 mutant mice could be a useful model to further our understanding of mcEDS pathophysiology and aid in the development of novel treatment strategies.